2006
DOI: 10.1007/s10529-006-9166-8
|View full text |Cite
|
Sign up to set email alerts
|

Assembling a novel bifunctional cellulase–xylanase from Thermotoga maritima by end-to-end fusion

Abstract: An artificial, bifunctional, thermostable cellulase-xylanase enzyme from Thermotoga maritima by gene fusion. The fusion protein exhibited both cellulase and xylanase activity when xynA was fused downstream of cel5C but no activities were shown when xynA was fused upstream of cel5C. The enzyme was optimally active at pH 5.0 and 80 degrees C over 30 min. E. coli expressed the fusion enzyme, with an apparent molecular mass of approximately 152 kDa by carboxymethyl cellulose- and xylan-SDS-PAGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…They found that the chimeric enzyme exhibited both cellulase and xylanase activity when Cel5Z was fused downstream of XynX, but no activities were observed when Cel5Z was fused upstream of XynX. A similar result was reported by Hong et al (2006). However, the chimeric enzymes constructed in these two previous studies did not contain linker sequences between the catalytic domains.…”
Section: Hydrolytic Activity Toward Rice Strawsupporting
confidence: 60%
See 2 more Smart Citations
“…They found that the chimeric enzyme exhibited both cellulase and xylanase activity when Cel5Z was fused downstream of XynX, but no activities were observed when Cel5Z was fused upstream of XynX. A similar result was reported by Hong et al (2006). However, the chimeric enzymes constructed in these two previous studies did not contain linker sequences between the catalytic domains.…”
Section: Hydrolytic Activity Toward Rice Strawsupporting
confidence: 60%
“…Chimeric enzymes are usually created by an end-to-end fusion technique, in which the N terminus of one catalytic domain is linked to the C terminus of the other catalytic domain (Khandeparker and Numan 2008). The sequential order of catalytic domains in chimeric enzymes may affect the enzyme specific activities Hong et al 2006). In addition, proper linker peptides between the individual catalytic domains are able to adopt the original conformation and maintain the functionality of the individual domains (Lu and Feng 2008).…”
Section: Design Of the Chimeric Xylanolytic Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Single polypeptides carrying more than one cellulolytic activity that have either been isolated from nature (12,29) or constructed in the laboratory (2,11,18,19,23,24) would certainly have advantages as candidate enzymes in the cellulase consortium.…”
mentioning
confidence: 99%
“…We and others have demonstrated that the creation of artificial, multifunctional, lignocellulosic hydrolases is a realistic and practical approach for the improvement of biomass conversion (5,8,9,12). These novel enzymes can be used alone, when a 1:1:1 stoichiometry is preferred, or in mixtures with small quantities of other enzymes to create an optimal enzyme cocktail when enzyme ratio FIG.…”
mentioning
confidence: 99%